Teka Teki (Jalili) Bahasa Kaili: Kajian Folklor Lisan dengan Pendekatan Hermeneutika - Masithah, Nona; Lembah, Gazali; Syam, Akhmad (Bahasantodea, 2024)
The objectives of the research are to analyze Kailinese Puzzle (Jalili): On analysis of Folklore Oral Expression through Hermeneutics Approach, to describe and to explain kinds of Kailinese puzzle, and to describe and to explain messages inside Kailines Puzzle (jalili). The research employs descriptive qualitative design. It was conducted at Kelurahan Baiya Kecamatan Tawaili involved 15 respondents. The data were collected through interview, questionnaire and document studies. The results of the study are (1) Jalili is divided into three kinds, a) Jalili in the form anecdocte. This kind of jalili covers the common joke in the society. It involves the questions about shifted real facts found in the society into the kind of questions in which they have particular humorous, b) Jalili that expresses about eagerness and willingness. This kind of jalili is particularly played by adults; among males and females. It is commonly found in any celebration parties, c) Jalili that concerns about life and Divinity. This kind of jalili contains advices about life and divinity. The players of jalili about life and divinity are the commonly the old men and adults. The adult asks about life and divinity to the old men, and the old men answer the question by offering it through jalili. 2) Jalili contains massages and advices; a) the allowable ways to talk to women, b) the allowable ways to deliver eagerness to the women, c) the allowable ways to visit women, d) to appreciate everything that contributes to human life, e) to act in polite manners to the parents, f) keep good relationship with others, g) knowing oneself to know God, and h) thanking to what God has provided us in the world.